Biochemical Study in Rats Hepatotoxicity with Carbon Tetrachloride and Treated with Camel Milk - Alyaa Majid (Journal of Global Pharma Technology, 2018)
Objective: Carbon tetrachloride (CCl4) is a highly toxic chemical agent. Therefore, the present study was carried out to investigate the protective effects of camel's milk against CCL4 induced toxicity in male rats. Materials and methods:  Albino male rats (150-200 g) were divided into four groups of 6 rats: a control group fed only with diet and tap water for two weeks, the second group fed with standard diet and camel milk, the third group intoxicated with CCl4 on first two days of the experimental 14 days and fed with tap water and diet, and the fourth group intoxicated with CCl4 on first two days of the experimental 14 days and then treated with camel milk. Results: The results indicated that the CCl4 caused a significant increased in the level of  serum total cholesterol(TC) , triglycerides(TG), very low density lipoprotein (VLDL)and low density lipoprotein(LDL), lactate dehydrogenase(LDH), creatine kinase(CK)and aspartate aminotransferase (AST). Also, there was a significant decreased in the level of serum high density lipoprotein (HDL).Protective activity of camel's milk against toxicity of CCl4  observed in decreasing of TC, TG, VLDL, LDL, LDH, CK, AST and increased in the HDL levels. Conclusion:  These findings strongly prove that beneficial effects of Camel Milk clearly shown through the reduction of the CCl4 induced related damages and oxidative stressKeywords: Camel milk, Carbon tetrachloride, Lipid profile, Rats.